Analysis of the Electrical Power Results from the Conversion of Cow Manure in a Biogas Power Plant - Agus Siswanto; Muhammad Rizal Ma’arif; Muhamad Soleh; Erfan Subiyanta (Mestro, 2022)
The need for renewable energy is urgently needed at this time to replace fossil energy as a source of electricity generation. The use of environmentally friendly renewable energy continues to be developed in order to deal with the energy crisis and create a healthy environment. The purpose of writing this final project is to analyze the electrical power resulting from the conversion of cow dung in a biogas power plant, so as to produce the efficiency value of biogas as a power plant. In this final project, electric power is generated from biogas and LPG gas which are converted using a generator set, after which the comparative values of biogas and LPG gas are obtained. The location of this research was conducted at a cattle farm in Girinata Village, Dukuntang District, Cirebon Regency. Calculations are made using varying loads, LPG gas fuel produces electricity that is quite stable compared to biogas which is still unstable. The stability of the electric power is generated due to the presence of high and stable fuel pressure, the more stable the pressure, the stable the generated electric power.